The Manifest Content dan Al-Ru'ya: Kondensasi Mimpi dalam Cerpen “Perempuan Patah Hati Yang Kembali Menemukan Cinta Melalui Mimpi” - Novia Adibatus Shofah; Haris Shofiyuddin; Diah Pitaloka (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study focuses on the same events that repeatedly appear in the main character's dreams. The contents of the dream are interpreted as instructions, so the main character carries out the instructions according to the contents of her dream and hopes it will come true. This study aims to discover how the manifest content and Al-Ru'ya appear as condensation of dreams in the short story Perempuan Patah Hati Yang Kembali Menemukan Cinta Melalui Mimpi by Eka Kurniawan. The method used in this study is qualitative, utilizing Sigmund Freud's dream interpretation theory. The data used are sentences that show the dream events experienced by the main character. The data analysis technique describes the condensation of dreams experienced by the main character. The study results show the condensation of dreams that first includes the manifest content, namely the repetition of dreams that appear clearly and are easy to remember due to the influence of physical products. The dream recurrence occurs due to a mental disorder characterized by hard feelings of trauma and sadness. Second, Al-Ru'ya, namely the belief in dreams that come true, such as finding a beach location on Pangandaran beach, meeting a handsome man and loving her, then becoming her future love, and the last is meeting the man's dog. Dreams come true because dreams are believed to be a realization of wishes, fulfil desires, perceptions and beliefs, and magical instructions.